Izvedba urbanih projektov po modelu javno-zasebnega partnerstva v Sloveniji - Mujkić, Sabina (Javna uprava, 2017)
The article analyzes the results of the first phase of a one-year research project Analysis of the Options For Implementing of Urban Projects Using Public-Private Partnership. It presents the key results of interviews with local authorities on one hand and investors on the other. The interviews' aim was to verify the existing practices in the field of Public-Private Partnerships (PPP) in Slovenia. The authors identify the motivations for and benefits of using the PPP mechanism in urban municipalities, and the risks and general obstacles to the implementation of urban projects according to the PPP model in Slovenia. They outline the public and private partners' perspectives on PPP projects and the approaches for overcoming the obstacles. The review of existing practices and interviews conducted with the representatives of Slovenian city municipalities and investors demonstrates the existence of a general interest in the implementation of urban projects using the PPP mechanism in Slovenia. However, the mechanism has not been adopted widely, but it is used only for the implementation of smaller urban projects. The most common types of executed urban projects or projects in the process of implementation of PPP in Slovenia are: energy renovation of publicly owned facilities, implementation of urban infrastructure projects, construction of sheltered housing, and the construction of facilities for education. In reviewing the situation in the field, the authors also emphasize some outstanding issues and dilemmas that arise in the financial implementation of the PPP projects at the municipal level.
Keywords: investicije; investitorji; investment; investors; javna korist; javno-zasebno partnerstvo; local authorities; lokalne oblasti; municipalities; občine; public benefit; public-privat partnership; risks; tveganja; urban projects; urbani projekti